Composite materials and bovine cortical bone drilling: thermal experimental analysis - Fernandes, Maria (2016)
The boné drilling is a common procedure in orthopaedic surgery, mainly in the treatment of fractures and reconstmctive surgery. The success of this surgeries is dependent of many factors and also in heat generation control during the drilling boné. The main concem in boné drilling are the mechanical and thermal damage of the boné induced by inappropriate parameters such as drill speed and feed-rate during surgical procedures. This paper studies the problem ofgeneration heat in drilling process ofcomposite materiais, with similar mechanical properties to the human boné, and in bovine cortical boné. The main goal was study the evolution of temperature through the different experimental methodologies using different drilling parameters. It was concluded when the drill speed and feed-rate are higher the boné temperature increase is lower. The results of temperature in the drilling process of composite material or bovine boné were compared and were found a good agreement with both.